The Effect Of Discharge Planning Combines Audiovisual With The Family Centered Nursing Preparedness Caring For Acute Post Stroke Patients - Nunuk Kurniati; Nursalam Nursalam; Yanis Kartini (Interest : Jurnal Ilmu Kesehatan, 2022)
Background: The low level of family readiness in caring patients at home was caused by limited implementation of discharge planning (DP) when entered the hospital (EH) or before leaved the hospital (LH), This intervention has an impact on improving nursing services. Methods: This study was mixed method study, the first stage used qualitative research with exploratory descriptive approach to 5 participants at RSI Sakinah. The population was families of post ASP at Sakinah Hospital were divided into the intervention group (33) and control (33) patient, using consecutive sampling sample selection by specifying subjects who meet the research criteria are included in the study for a certain period of time, so that the number of respondents can be met. The independent variable was CADP. The dependent variable was FR to care post ASP. Data were collected using a modified FR questionnaire and analysed using Kolmogorov Smirnov, Wilcoxon sign rank, Mann Whitney. Results: The first phase of the study produced a CADP module for families of stroke patients, the second phase based on the Wilcoxon sign rank test showed that there was an effect after the intervention and Mann Whitney test showed the difference significant mean between intervention and control during EH (0.000; 0.000), during treatment (0.000;0.000), before LH (0.000;0.000). Conclusion: The CADP module and intervention increased FR to care ASP patients during EH, treatment and LH so they can be used as guides and media in providing DP education in hospitals for patients' families.